The problem of health preservation in the history of educational thought (Pedagogy of Higher and Secondary Education, 2016)
Kuchurgan Ye. V. The problem of health preservation in the history of educational thought.The article analyses the history of problems of health preservation. The purpose of the article is to show the development of health preservation in different historical period of educational thought formation. Features of health preservation as part of the educational thought of society are highlighted. Fundamental bases of historical experience of healthy technology in educational processes of various public formations are revealed. Leading tendencies of a national education system combined with changes in understanding of a role of the teacher in processes of health preservation have been defined. At civilized approach the main function of health preservation is an active resistance to influence of hostile environment, such as the human person and society. Training of students in safety measures of existence in hostile environment is the main component of health preservation in pedagogics; where continuous improvement of school and university education is basic. A general education where the leading role is given to the teacher who owns humanistic pedagogics of the self-identification based on the principles: nature correspondence and culture correspondence has to be applied. The philosophical fundamentals of the harmonious development of personality and her life are examined. The dynamics of disease overcoming as a process of scientific work is shown.It has been proved that Ukraininan National Pedagogical School of health preservation has to be grounded on a study of a history of people at school and educational system which corresponds the traditions. Based on the historical development of the nation, children should be linked to their land and their native culture, and participate in creating the image of the ideal human being as a citizen of Ukraine.
Keywords: health; health preservation; pedagogical idea of healthy technology; personality; harmonious development; human activity